2019
DOI: 10.1093/eurheartj/ehz896
|View full text |Cite
|
Sign up to set email alerts
|

Complete revascularization reduces cardiovascular death in patients with ST-segment elevation myocardial infarction and multivessel disease: systematic review and meta-analysis of randomized clinical trials

Abstract: Aims The aim of this work was to investigate the prognostic impact of revascularization of non-culprit lesions in patients with ST-segment elevation myocardial infarction (STEMI) and multivessel disease by performing a meta-analysis of available randomized clinical trials (RCTs). Methods and results Data from six RCTs comparing complete vs. culprit-only revascularization in STEMI patients with multivessel disease were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 28 publications
4
49
1
1
Order By: Relevance
“…Another recently published meta-analysis which also included the data of the COMPLETE trial showed, in contrast to our meta-analysis, a significant reduction of cardiovascular mortality with complete revascularization [ 22 ]. This discrepancy results from different statistical approaches.…”
Section: Discussioncontrasting
confidence: 82%
“…Another recently published meta-analysis which also included the data of the COMPLETE trial showed, in contrast to our meta-analysis, a significant reduction of cardiovascular mortality with complete revascularization [ 22 ]. This discrepancy results from different statistical approaches.…”
Section: Discussioncontrasting
confidence: 82%
“…possible. In this regard, the prognostic relevance of a timely complete coronary revascularization has been repeatedly demonstrated [41][42][43]. Finally, the new non-invasive MWI might be a more sensitive and precise alternative to visual assessment to distinguish between segments that benefited and did not benefit from PCI.…”
Section: Plos Onementioning
confidence: 97%
“…[20][21][22] However, randomized trial data supporting complete revascularization is only available for ST-elevation myocardial infarction (STEMI) patients undergoing primary PCI, where complete revascularization of significant nonculprit lesions reduces cardiovascular events. 21,23 If complete revascularization by PCI is indicated, a careful assessment of the risk and benefit of this approach is required to optimize patient safety. For patients with multivessel disease, this may require noninvasive ischemia or viability testing, invasive coronary physiologic testing, and considering staged revascularization to reduce the risk of any single procedure.…”
Section: Multivessel Coronary Disease and Importance Of Complete Rementioning
confidence: 99%
“…Furthermore, complete revascularization in the presence of multivessel CAD is associated with improved long-term clinical outcomes in STEMI. 21,23 Whether complete revascularization should be performed in patients with non-STEMI remains unknown, but maybe supported by observational data. 33 Staging procedures for the treatment of non-culprit stenoses appears to be safe if performed in a timely fashion.…”
Section: High Predicted Mortality By Sts And/or Syntax II Score Andmentioning
confidence: 99%
See 1 more Smart Citation